2005
DOI: 10.1074/jbc.m508425200
|View full text |Cite
|
Sign up to set email alerts
|

Importin KPNA2 Is Required for Proper Nuclear Localization and Multiple Functions of NBS1

Abstract: Nijmegen breakage syndrome (NBS) is a chromosomal-instability syndrome associated with cancer predisposition, radiosensitivity, microcephaly, and growth retardation. The NBS gene product, NBS1, is a component of the MRE11-RAD50-NBS1 (MRN) complex, a central player associated with double strand break (DSB) repair. In response to radiation, NBS1 is phosphorylated by ATM, and the MRN complex relocalizes to form punctate nuclear foci for DNA repair. NBS1 controls both the nuclear localization of the MRN complexes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 45 publications
2
85
0
Order By: Relevance
“…Cells were grown at 30°C in yeast extract peptone dextrose (YPD) broth. Cell lysates were prepared with lysis buffer (150 mM NaCl, 1% Nonidet P-40, 1% deoxycholate, 0.1% SDS, 50 mM TrisHCl, pH 7.5, and protease inhibitors) or trichloroacetic acid (TCA) precipitated 63 . Whole proteins were extracted and resolved by 10% (except Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were grown at 30°C in yeast extract peptone dextrose (YPD) broth. Cell lysates were prepared with lysis buffer (150 mM NaCl, 1% Nonidet P-40, 1% deoxycholate, 0.1% SDS, 50 mM TrisHCl, pH 7.5, and protease inhibitors) or trichloroacetic acid (TCA) precipitated 63 . Whole proteins were extracted and resolved by 10% (except Fig.…”
Section: Methodsmentioning
confidence: 99%
“…This complex consisting of MRE11, RAD50, and NBS1 forms nuclear foci that are required for DNA double strand break repair. Irradiation of HeLa cells (15 Gy) resulted in increased nuclear activity of MRN and DNA repair (36). Interestingly, incubation of HSC45-M2 cells with the a-emitter 213 Bi decreased KPNA2 expression, implying a reduction of MRN-mediated double strand break repair.…”
Section: Discussionmentioning
confidence: 99%
“…Down-regulation of these genes is in accordance with the occurrence multinucleated/mitotic catastrophe cells. KPNA2 also mediates nuclear localization of the MRN complex in response to radiation (36). This complex consisting of MRE11, RAD50, and NBS1 forms nuclear foci that are required for DNA double strand break repair.…”
Section: Discussionmentioning
confidence: 99%
“…35 Blyth et al 13 suggested that deletion of KPNA2 accounted for the phenotypic characteristics of their patient (short stature, microcephaly, syndactyly, clinodactyly and intellectual disability), which could not be explained by Carney Complex. 13,36 In patient 4, the contribution of KCNJ2 (Inward rectifier potassium channel 2, subfamily J), for which heterozygous mutations are reported to be responsible for Long QT syndrome type 7 also known as Andersen syndrome (OMIM no. 170390), cannot be excluded.…”
Section: Skin and Teethmentioning
confidence: 99%